Faktor Yang Mempengaruhi Perkembangan Motorik Kasar Anak 3-5 Tahun di Desa Lasara Sawo Kecamatan Sawo Kabupaten Nias - Dina Hura; Yanti Jernih Gea; Selvin Syukur Gea (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background. Gross motor development of children from an early age can detect if there is an abnormality. This needs to be evaluated for cause as it will be affect the child's gross motor skills in the future. Research purposes. To analyze the factors that influence gross motor development in children aged 3-5 years in Lasara Sawo Village. Research design. cross sectional. Population and Sample.All parents who have toddlers aged 3-5 years totaled 35. Instrument. KPSP, questionnaires and scales. Data analysis. Chi-Square. Research result. There is a relationship parenting style, motivation and nutritional status to gross motor development (<0.05). The most dominant influential variable is the authoritarian parenting style Odd Ratio of 11,000 and a sig.(P Value) of 0.007 (<0.05). Suggestion. In providing effective education about gross motor development, it should adjust to the parenting style, motivation and nutritional status of the target.